(untitled) (Bangladesh Journal of Obstetrics & Gynaecology, 2020)
Background: Currently preterm labour is one of the most challenging problems confronting the obstetricians and perinatologists. This unfortunate episode accounts for 50-75% of the perinatal mortality. Methods: A cross sectional study was conducted on 210 pregnant women with preterm labour admitted in Monno Medical College Hospital, Manikganj from June 2014 to December 2015, to study the causes and outcome of preterm birth in Tertiary health centre of Manikganj. Results: Occurence of preterm birth was 13.82%; 47.14% occured between 34-37 weeks of gestation; 33.80% occured 31-33 weeks of gestation and occurred in 28-30 weeks 19.04%. About 22% patients presenting with preterm labour had a past history of abortions and 14.3% had a history of preterm delivery. Premature rupture of membranes was found to be the most common risk factor related with preterm labour in the present pregnancy. Genitourinary tract infection was the next important risk factor of preterm labour; 24.8% (86) patients had either vaginal infection (19.5%) or urinary infection (21.4%) or both. Another important risk factor identified in this study was antepartum haemorrage which was cause in 11.4 % cases. Preterm babies commonly suffered from various complications like jaundice (32.1%), respiratory distress syndrome (22.6%), asphyxia (13.5%), sepsis, hypoglycemia and coagulopathy. Conclusion: Most of the preterm births occured between 34-37 weeks of gestation. Most common risk factors of preterm births are history of abortion and preterm delivery in previous pregnancy; PROM UTI vaginal infection, PIH and APH in correct pregnancy. Newborn jaundice, RDS and birth asphyxia are the common neonatal morbidity in preterm labour. Identifying risk factors to prevent the onset of preterm labour and advanced neonatal care unit can help decrease neonatal morbidity and mortality. Bangladesh J Obstet Gynaecol, 2017; Vol. 32(2) : 90-93